THE ANALYSIS OF THE MAIN CHARACTER IN SHORT STORY THE HUSBAND STITCH BY CARMEN MARIA MACHADO - Rizki Ananda, Maulana Alfian (Linguistik, Terjemahan, Sastra (LINGTERSA), 2023)
The study entitled The Analysis of the Main Character in Short Story The Husband Stitch by Carmen Maria Machado is aimed to find out the psychological, sociological, and physiological dimensions of the main character and the methods of characterization used by the author to present the main character in this story. There were some theories used in this study such as the theory about characterization by Griffith (1982), and the theory about the dimension of character by Wellek and Warren (1955). The author uses a direct method to represent the main character to the readers. After analyzing, the author describes the main character of â€œIâ€ as a beautiful girl who comes from a good family. She has some secret about the ribbon on her neck, and she does not want someone else to know about it, even her husband. The main character in this story experienced a dynamic character. The main character of â€œIâ€, who at first did not want to show what was behind her green ribbon, finally changed her mind and showed what she had been hiding from her husband.